Analysis of Language Style in Pantun Nasihat: A Stillistic Study - Rizkita Rodearni; Rosmawaty Harahap (Winaya Inspirasi Nusantara Foundation, 2025)
Pantun is a very popular genre of oral literature in public Malay. Language is one culture in our country This, Language is also included identity of our country This. Stylistic studies are branch linguistics that studies style Language in literary works, including pantun. One of regional literary forms that is poetry (poetry ancient) is an oral and divided literature in several in the form of mantras, pantuns, poetry, and Gurindam. Literary works in regions have a big influence on culture area the. Literary works are also influenced by the creativity and imagination of each writer. Literary works in public works also for need religion, advice, custom customs and entertainment. The guide works as education and entertainment because the poem contains tips and advice, can also be used for just entertain self. Pantun is used in various events have various meaning for sure in accordance with the event being hosted. Pantun no must use in events, but rhymes can also be used be the medium of delivery advice. Rhymes in everyone the concept own uniqueness each in writing the line. In research this, we will analyze style language used in a poem of advice with approach stylistics. With analyze style Language in a poem of advice through approach stylistics, research This expected can give deep understanding about How aspect language utilized in a way aesthetic and effective in convey message or advice. Additionally, research this also contributes to preserve and appreciate treasures of oral literature Malay.